Garyounis University Professors' Research Activities:Motivations, Ubstacles and Development Suggestions - الرقادي , ميكائيل إدريس; الكاديكي , أماني عبدالحفيظ (Dirasat in Economics and Business, 2005)
It is obvious that the scientific research is one of the significant activities. The university staff me mbers are concerned with this activity ; hence, the present study tackles this issue shedding light on research activities at the univ ersity level, the obstacles that the university professors face as they conduct researches and the sugg estions for develop-ping research.